2017
DOI: 10.1007/s41252-017-0033-5
|View full text |Cite
|
Sign up to set email alerts
|

Distress and Psychological Growth in Parenting an Adult Child with Autism Spectrum Disorder and Aggression

Abstract: Parenting an adult child with autism spectrum disorder (ASD) who has intermittent outbursts of aggression may expose parents and other family members to potential physical threat and psychological distress including chronic hypervigilance. However, no known studies have explored the 'lived' experience of parenting an adult child diagnosed with ASD who displays aggression. Therefore, this phenomenological study sought both negative and positive subjective interpretations of three parents of adult sons with ASD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Novak and Guest (1989) described four types of burden (time dependence, financial, developmental, and emotional) that contribute to caregiving-related stressors. Parents reported that meeting the needs of their adult children with ASD is time-consuming, as well as physically and emotionally exhausting (Swaab et al, 2017). Because their adult child with ASD might never leave home, many parents recognized that their developmental milestones differed from their peers who were experiencing empty nest syndrome or having grandchildren (Marsack & Perry, 2018).…”
Section: Caregiver Burdenmentioning
confidence: 99%
“…Novak and Guest (1989) described four types of burden (time dependence, financial, developmental, and emotional) that contribute to caregiving-related stressors. Parents reported that meeting the needs of their adult children with ASD is time-consuming, as well as physically and emotionally exhausting (Swaab et al, 2017). Because their adult child with ASD might never leave home, many parents recognized that their developmental milestones differed from their peers who were experiencing empty nest syndrome or having grandchildren (Marsack & Perry, 2018).…”
Section: Caregiver Burdenmentioning
confidence: 99%
“…For purposes of the present study, caregiver burden entails the demands, challenges, and stressors experienced by those who care for an adult child with ASD and/or an additional loved one (Lazarus & Folkman, 1984). Providing care to adult children with ASD can be exhausting and time-intensive for parental caregivers (Oti-Boadi et al, 2020; Swaab et al, 2017). Many compound and noncompound caregivers are tasked with the unrelenting nature of providing care, while trying to balance everyday life, work, and social responsibilities (Hines et al, 2014; Nicholas et al, 2020; Perkins, 2010, 2011).…”
Section: Caregiver Burdenmentioning
confidence: 99%
“…Most of the studies focused on negative outcomes such as the caregiver burden, depression, health issues, etc. Several studies focused on outcomes and their correlation with child‐specific factors; symptom severity (e.g., Marsack‐Topolewski & Maragakis, 2021), challenging behaviour (e.g., Swaab et al, 2017), ADL (e.g., Marsack‐Topolewski, Samuel, & Tarraf, 2021) and age (e.g., Burke & Heller, 2016). Other parental‐specific factors studied included marital satisfaction (Hartley et al, 2012), daily stressors (e.g., Smith et al, 2010), worries about the future (e.g., Oti‐Boadi et al, 2020), support (Griffith et al, 2012; Smith et al, 2012) and financial issues (e.g., Marsack & Perry, 2018), and so forth.…”
Section: Discussionmentioning
confidence: 99%
“…symptom severity (e.g., Marsack-Topolewski & Maragakis, 2021), challenging behaviour (e.g., Swaab et al, 2017), ADL (e.g., Marsack-Topolewski, Samuel, & Tarraf, 2021) and age (e.g., Burke & Heller, 2016).…”
Section: Discussionmentioning
confidence: 99%